A method for probe coating preparation for scanning capacitance microscopy testing

CN123009318APending Publication Date: 2026-10-30SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611154469.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]鉴于上述现有技术的不足,本发明的目的在于用于扫描电容显微镜测试的探针镀层,旨在解决现有探针难以同时满足电荷阻挡注入与维持电容敏感性的需求的问题

Benefits of technology

[0014]有益效果:本发明提供了一种用于扫描电容显微镜测试的探针镀层,本发明采用原子层沉积工艺,对原子层沉积设备进行精准分段控温,在导电探针基底表面制备厚度可控、台阶覆盖优异的超薄氧化铪HfO2阻挡层,本发明制备得到的用于扫描电容显微镜测试的探针镀层能同时满足电荷阻挡注入与维持电容敏感性的需求,多次扫描(200-1000s)中dc/dV振幅和电容信号稳定(平均值更高、标准差/阿尔佩偏差更小)。氧化铪HfO2阻挡层作为高k介质层,在测量时,可原位构建完整稳定的金属-氧化物-半导体(MOS)测试结构,从物理隔离层面阻断探针与半导体裸表面之间的电荷注入通道,允许可靠C-V测量(偏压-3至0V下重复曲线一致)。CAFM测试显示镀层完整(电流~pA级,噪声主导)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123009318A_ABST
    Figure CN123009318A_ABST
Patent Text Reader

Abstract

The application relates to the field of nanomaterial characterization, and in particular to a probe coating preparation method for scanning capacitance microscope testing. The preparation method comprises the following steps: fixing a conductive probe substrate on a wafer base; heating a hafnium source precursor delivery valve group to 120-140 DEG C; heating a process reaction cavity to 150-350 DEG C; heating the wafer base with the fixed conductive probe to 150-350 DEG C; introducing the hafnium source precursor into the reaction cavity, performing 50-100 complete deposition cycles, depositing a hafnium oxide barrier layer on the surface of the conductive probe substrate, and obtaining the probe for scanning capacitance microscope testing. The application performs accurate segmented temperature control on an atomic layer deposition device, prepares a super-thin hafnium oxide HfO2 barrier layer with controllable thickness and excellent step coverage on the surface of the conductive probe substrate, the barrier layer can meet the requirements of charge blocking injection and maintaining capacitance sensitivity, the dc / dV amplitude and the capacitance signal are stable in multiple scans, a complete and stable MOS test structure can be constructed in situ, and reliable C-V measurement is allowed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanomaterial characterization, and more particularly to a method for preparing a probe coating for scanning capacitance microscopy testing. Background Technology

[0002] Scanning capacitance microscopy (SCM) is an important tool for nanoscale characterization of the electrical properties of two-dimensional materials (such as MoS2). However, traditional pure Pt probes have significant limitations in practical MOS structure testing: although pure Pt probes have good conductivity, they exhibit poor stability when bonded to high-k dielectric layers such as HfO2. With increasing scan counts, the dc / dV amplitude decreases significantly (reported in the literature to be over 50%), mainly because the applied voltage to the substrate forms a conductive path with MoS2, triggering a severe charge injection effect, leading to distorted CV curves, poor test repeatability, and a high failure rate. While existing technologies include insulating probes, they generally sacrifice conductivity or cannot achieve atomically uniform plating, making it difficult to simultaneously meet the requirements of blocking injection and maintaining capacitive sensitivity, greatly limiting their application in the characterization of 2D material devices.

[0003] Therefore, existing technologies need to be improved. Summary of the Invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a probe coating for scanning capacitance microscopy testing, which aims to solve the problem that existing probes cannot simultaneously meet the requirements of charge blocking injection and maintaining capacitance sensitivity.

[0005] The technical solution of the present invention is as follows: In a first aspect, the present invention provides a method for preparing a probe coating for scanning capacitance microscopy testing, comprising the following steps: S1. Provide a conductive probe substrate and use atomic layer deposition process to fix the conductive probe substrate on the wafer base of the atomic layer deposition equipment; S2. Heat the hafnium source precursor delivery valve bank to 120-140°C (for vaporizing the hafnium source precursor); heat the process chamber to 150-350°C; heat the wafer pedestal that holds the conductive probe substrate to 150-350°C. S3. Introduce the hafnium source precursor into the reaction chamber and perform 50-100 complete deposition cycles to deposit a hafnium oxide barrier layer on the surface of the conductive probe substrate, thereby obtaining the HfO2-coated platinum probe for MoS2 scanning capacitance microscopy testing.

[0006] It should be noted that the present invention uses atomic layer deposition to prepare a hafnium oxide insulating coating on a conductive probe substrate.

[0007] Optionally, the hafnium source precursor is tetra(dimethylamino)hafnium, tetra(ethylmethylamino)hafnium, or tetra(diethylamino)hafnium.

[0008] Optionally, the conductive probe substrate is pure Pt. It has a spring constant of 22 N / m, a frequency of 21 kHz, a length of 300 μm, a width of 100 μm, a thickness of 5 μm, and is a rectangular solid wire.

[0009] Optionally, the thickness of the hafnium oxide barrier layer is 3-10 nm.

[0010] Optionally, a single complete deposition process includes: a hafnium source precursor pulse and an oxidant pulse.

[0011] Optionally, the hafnium source precursor pulse time is 40-400ms, and the oxidant pulse time is 30-60ms.

[0012] Optionally, the oxidant is H2O.

[0013] Secondly, the present invention provides a probe coating for scanning capacitance microscopy testing, which is prepared by the aforementioned preparation method.

[0014] Beneficial Effects: This invention provides a probe coating for scanning capacitance microscopy (SCM) testing. Employing atomic layer deposition (ALD) technology with precise segmented temperature control of the ALD equipment, an ultrathin hafnium oxide (HfO2) barrier layer with controllable thickness and excellent step coverage is prepared on the surface of a conductive probe substrate. The probe coating prepared by this invention simultaneously meets the requirements of charge blocking injection and maintaining capacitance sensitivity. During multiple scans (200-1000s), the dc / dV amplitude and capacitance signal remain stable (higher average value, smaller standard deviation / Alpe bias). As a high-k dielectric layer, the hafnium oxide (HfO2) barrier layer can construct a complete and stable metal-oxide-semiconductor (MOS) test structure in situ during measurement, physically isolating the charge injection channel between the probe and the bare semiconductor surface, allowing reliable CV measurements (consistent repeatable curves from -3 to 0V bias). CAFM testing shows the coating is intact (current ~pA level, noise dominant). Attached Figure Description

[0015] Figure 1 This is a process flow diagram for preparing the probe coating for scanning capacitance microscopy testing according to an embodiment of the present invention.

[0016] Figure 2 This is a photograph of the probe prepared for scanning capacitance microscopy testing in Example 1.

[0017] Figure 3Image of molybdenum disulfide on a gold substrate.

[0018] Figure 4 This is a synchronous imaging image of a MoS2 thin film obtained by three consecutive in-situ scans using a pure Pt conductive probe without a protective layer.

[0019] Figure 5 This is a synchronous imaging image of the MoS2 thin film obtained by three consecutive in-situ scans of the probe coating for scanning capacitance microscopy testing in this embodiment.

[0020] Figure 6 This is a comparison chart showing the standard deviation of the dC / dV amplitude signal as a function of scan duration.

[0021] Figure 7 This is a comparison chart of the standard deviation of the capacity signal over time.

[0022] Figure 8 The image shows the results of two single-point CV (SCM) scans performed on the same location in MoS2 using the probe from Example 1.

[0023] Figure 9 shows the results of two single-point CV repeat scans of the same location on MoS2 using an uncoated pure Pt probe.

[0024] Figure 10 A comparison of IV curves for probes with HfO2 coatings of different thicknesses. Detailed Implementation

[0025] This invention provides a probe coating for scanning capacitance microscopy testing. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0026] In existing scanning capacitance microscopy characterization systems for two-dimensional van der Waals semiconductors, both mainstream probe schemes have inherent process defects, making them unsuitable for high-precision MOS structure testing of materials without natural oxide layers, such as MoS2. The first type is the pure platinum-iridium conductive probe without an insulating layer. This type of probe relies solely on the sample's own oxide layer to construct the MOS test structure. When the surface of the two-dimensional semiconductor being tested lacks a native insulating layer, the probe metal directly contacts the semiconductor, forming a metal-semiconductor contact structure. Under an applied DC bias, charge injection is easily generated. During multiple consecutive scans, the injected charge continuously alters the intrinsic carrier concentration on the surface of the two-dimensional material. Macroscopically, this manifests as a continuous decay of the dC / dV signal amplitude with the number of scans, irreversible distortion of the CV characteristic curve, and extremely poor data consistency from repeated tests on the same sample, making it impossible to obtain stable and reliable intrinsic electrical parameters. The second type is the commercially available insulating-coated modified probe, whose insulating coating is mostly prepared using physical deposition processes such as magnetron sputtering and electron beam evaporation. This type of deposition method lacks self-limiting growth characteristics and has poor step coverage for the nano-curvature microstructures at the probe tip. It is prone to defects such as thinning of the coating at the tip, local pinholes, and exposure of the metal substrate, and cannot completely isolate charge injection. If the leakage current problem is compensated by thickening the coating, it will significantly increase the series capacitance on the probe side, significantly reducing the capacitance detection sensitivity and making it difficult to achieve accurate imaging of the nanoscale carrier distribution of two-dimensional materials. At the same time, the existing insulating coating preparation process does not match a dedicated low-temperature segmented temperature control system for AFM microcantilever probes. During the coating deposition process, problems such as uneven decomposition of precursors and large film thickness dispersion are prone to occur, making it difficult to mass-produce dedicated SCM probes with uniform thickness and a balance between insulation performance and detection sensitivity.

[0027] In summary, traditional pure platinum probes suffer from severe charge injection, significant attenuation of dC / dV signals, distortion of CV electrical curves, and poor test repeatability when testing two-dimensional van der Waals semiconductors. In addition, existing insulating probes have shortcomings such as insufficient coating uniformity and excessive signal sensitivity loss.

[0028] Based on this, this embodiment provides a method for preparing a probe coating for scanning capacitance microscopy testing, such as... Figure 1 As shown, it includes the following steps: S1. Provide a conductive probe substrate and use atomic layer deposition process to fix the conductive probe substrate on the wafer base of the atomic layer deposition equipment; S2. Heat the hafnium source precursor delivery valve bank to 120-140°C (for vaporizing the hafnium source precursor); heat the process chamber to 150-350°C; heat the wafer pedestal that holds the conductive probe substrate to 150-350°C. S3. Introduce the hafnium source precursor into the reaction chamber and perform 50-100 complete deposition cycles to deposit a hafnium oxide barrier layer on the surface of the conductive probe substrate, thereby obtaining the HfO2-coated platinum probe for MoS2 scanning capacitance microscopy testing.

[0029] It should be noted that this invention uses atomic layer deposition (ALD) to prepare a hafnium oxide insulating coating on the surface of a conductive probe. The ALD equipment used is the TEM-150 from Xiamen Yunmao Technology Co., Ltd. The precursor delivery valve assembly is heated to 120-140°C, primarily to ensure sufficient vaporization and stable delivery of the precursor, while preventing condensation or decomposition in the pipeline. The reaction chamber and wafer substrate are heated to 150-350°C because this temperature range corresponds to the "temperature window" of the ALD process. Within this range, the film growth rate is stable, the film quality is excellent, and a self-limiting surface reaction can be achieved.

[0030] This invention employs atomic layer deposition (ALD) technology with precise segmented temperature control of the ALD equipment to fabricate an ultrathin hafnium oxide (HfO2) barrier layer on the surface of a conductive probe substrate. This layer exhibits controllable thickness and excellent step coverage. The probe prepared by this invention for scanning capacitance microscopy (SCM) simultaneously meets the requirements for charge blocking injection and maintaining capacitance sensitivity. During multiple scans (200-1000 s), the dc / dV amplitude and capacitance signal remain stable (higher average value, smaller standard deviation / Alpe bias). As a high-k dielectric layer, the hafnium oxide (HfO2) barrier layer allows for the in-situ construction of a complete and stable metal-oxide-semiconductor (MOS) test structure during measurement, physically isolating the charge injection channel between the probe and the bare semiconductor surface, enabling reliable CV measurements (consistent repeatable curves from -3 to 0 V). CAFM testing shows complete coating (current ~pA level, noise dominant).

[0031] This invention employs atomic layer deposition (ALD) technology, which differs from conventional thin film preparation methods such as sputtering and evaporation. ALD relies on its self-limiting surface reaction characteristics to form an atomically uniform and continuous insulating film at the nano-curvature morphology of the probe tip, avoiding leakage defects caused by local metal exposure. Simultaneously, by limiting the three-stage isothermal window of precursor delivery, cavity, and wafer substrate, and combining it with standardized precursor pulse, inert gas purging, and oxidant cycling sequence, the total thickness of the hafnium oxide coating is precisely controlled to 3-10 nm. While ensuring sufficient insulation barrier capability, it minimizes the attenuation of the dC / dV detection signal by the series capacitance, balancing charge injection suppression effect and nanoscale capacitance detection sensitivity.

[0032] In some embodiments, the hafnium source precursor is tetra(dimethylamino)hafnium, tetra(ethylmethylamino)hafnium, or tetra(diethylamino)hafnium.

[0033] In some embodiments, the conductive probe substrate is pure Pt.

[0034] In some embodiments, the spring constant is 22 N / m, the frequency is 21 kHz, the length is 300 μm, the width is 100 μm, the thickness is 5 μm, and it is a rectangular solid wire.

[0035] In some embodiments, the thickness of the hafnium oxide barrier layer is 3-10 nm.

[0036] In some embodiments, a single complete deposition process includes: a hafnium source precursor pulse and an oxidant pulse.

[0037] In some embodiments, the hafnium source precursor pulse duration is 40-400 ms, and the oxidant pulse duration is 30-60 ms.

[0038] In some embodiments, the oxidant is H2O.

[0039] Secondly, the present invention provides an HfO2-coated platinum probe for MoS2 scanning capacitance microscopy testing, which is prepared by the aforementioned preparation method.

[0040] The present invention will be further described below through specific embodiments.

[0041] Example 1 A method for preparing a probe coating for scanning capacitance microscopy testing, such as Figure 1 As shown, it includes the following steps: S1. Provide a conductive probe substrate and use atomic layer deposition process to fix the conductive probe substrate on the wafer base of the atomic layer deposition equipment; S2. Heat the hafnium source precursor delivery valve bank to 130.0°C (for vaporizing the hafnium source precursor); heat the process chamber to 200.0°C; heat the wafer pedestal that holds the conductive probe to 200.0°C; S3. Introduce the hafnium source precursor into the reaction chamber and perform 50 complete deposition cycles to deposit a hafnium oxide barrier layer on the surface of the conductive probe substrate, thereby obtaining the probe used for scanning capacitance microscopy testing.

[0042] The hafnium source precursor is 3-TDMAHf.

[0043] The conductive probe substrate is pure Pt; its spring constant is 22 N / m, its frequency is 21 kHz, its length is 300 μm, its width is 100 μm, its thickness is 5 μm, and it is a rectangular solid wire.

[0044] The thickness of the hafnium oxide barrier layer is 5 nm.

[0045] A single complete deposition process includes: a hafnium source precursor pulse and an oxidant pulse. The hafnium source precursor pulse duration is 100 ms, and the oxidant pulse duration is 50 ms.

[0046] The oxidant is H2O.

[0047] The HfO2-coated platinum probe obtained in this embodiment for MoS2 scanning capacitance microscopy testing is as follows: Figure 2 As shown. Figure 3 This is an image of molybdenum disulfide on a gold substrate (optical microscope), which shows the initial surface morphology of MoS2 on the gold substrate.

[0048] The above-mentioned two-dimensional MoS2 thin film region was scanned in three consecutive rounds using conductive atomic force microscopy (C-AFM, differential capacitance dC / dV imaging mode). Three types of channel signals were acquired simultaneously: morphological height, differential capacitance amplitude (dC / dV), and interface capacitance. The only variable was the protective structure of the conductive probe surface, which was used to quantitatively verify the influence of metal tip oxidation / contamination on the stability of two-dimensional semiconductor electrical imaging. Figure 4 Simultaneous in-situ scanning images of MoS2 thin films by a pure Pt conductive probe without a protective layer, after three consecutive rounds of imaging. Figure 5 The images show the simultaneous in-situ scanning images of the HfO2-coated platinum probe used for MoS2 scanning capacitance microscopy testing in this embodiment. From left to right, they represent the morphology height, differential capacitance amplitude (dC / dV amplitude), and interface capacitance channels. From top to bottom, they represent the results of the first to third consecutive scanning rounds.

[0049] The test sample is Figure 3 The MoS2 thin film with stepped boundary shown is observed in the same boundary area using a 1μm scale, allowing for a direct comparison of morphology, electrical contrast, and signal drift during continuous scanning.

[0050] from Figure 4 As can be seen from the left (Height channel), the overall contour of the topography did not undergo significant deformation after three rounds of scanning. Only the grayscale scale range in the third round shifted from ±31.5nm to ±35.5nm: the wear of the bare Pt tip and the surface oxide layer had a weak effect on the short-range mechanical repulsion, and the geometric morphology of the sample surface steps and wrinkles could be stably acquired; however, the slow rounding of the tip tip would change the zero point of the cantilever feedback, causing a slight shift in the height scale, with only a slight distortion in the topography contrast. From Figure 4The dC / dV amplitude differential capacitance channel shows the following: First scan: only a weak purple contrast (low amplitude signal) at the edge of the MoS2 boundary on the left, while the main substrate is a low-amplitude brownish-red; Second scan: a large area on the left side of the boundary shows a significant high-amplitude purple contrast, with a substantial increase in electrostatic / interface dielectric signals; Third scan: the entire left area becomes a strong purple high-amplitude signal, with an irreversible overall shift in contrast. This is because the bare Pt tip continuously generates an ultrathin PtO / PtO2 oxide layer under atmospheric conditions, scanning bias, and cantilever friction, while simultaneously adsorbing environmental moisture, hydrocarbon pollutants, and MoS2 exfoliation debris. The oxide / adsorption layer alters the tip surface work function and equivalent dielectric thickness, causing continuous changes in the electrostatic force and differential capacitance between the tip and sample, directly reflected in the dC / dV vibration amplitude imaging. The tip surface state changes irreversibly with each scan. Figure 4 As can be seen in the right (Capacitance imaging channel), the capacitance grayscale scale value continuously declines unidirectionally: the first round scale is 715–718mV → the second round is 712–714mV → the third round is 707–709mV, with the overall capacitance signal decreasing by nearly 10mV across the three rounds; simultaneously, the horizontal stripe noise within the image gradually intensifies, and the capacitance contrast difference on both sides of the MoS2 step continuously changes. The differential capacitance signal is jointly determined by the tip-MoS2 interface dielectric layer, surface carrier concentration, and contact barrier. The insulating oxide layer continuously growing on the surface of the bare Pt tip is equivalently connected in series with the interface capacitance system, continuously reducing the interface capacitance response value obtained from the test; moreover, the tip curvature increases with wear, changing the local detection area, further exacerbating the capacitance contrast drift, making multi-round continuous quantitative characterization impossible. From Figure 4 It can be seen that unprotected pure Pt tips are not suitable for long-term, multi-round continuous electrical imaging of MoS2: the mechanical morphology signal only drifts slightly, but the dC / dV amplitude and capacitance signals undergo irreversible and large-scale shifts and contrast distortions as the scanning process progresses, making it impossible to repeatedly acquire reliable surface electrical distribution data.

[0051] Figure 5 As can be seen from the left (Height channel), the boundary contours of the three morphologies completely overlap, with only the grayscale scale of the third morphology being slightly adjusted to ±29.0nm. There is no contrast distortion in the step and edge morphology. The hardness of the HfO2 coating is higher than that of pure Pt, which suppresses the wear of the needle tip and the zero point of the mechanical morphology feedback has almost no drift. Figure 5As can be seen from the (dC / dV amplitude differential capacitance amplitude channel), the contrast distribution of the three waves is highly consistent: the purple high-amplitude region to the left of the MoS2 boundary shows almost no change in range and brightness, while the amplitude of the brownish-red region on the substrate is stable, with no large-area contrast abrupt changes. The dense HfO2 coating isolates the Pt substrate from the atmosphere and sample debris, completely preventing oxidation and contaminant adsorption on the tip surface. The work function of the tip surface and the equivalent dielectric layer thickness at the tip remain constant during continuous scanning. The electrostatic force and differential force between the tip and MoS2 are stable, and the amplitude imaging is repeatable. From Figure 5 As can be seen from the right side (Capacitance imaging channel): the drift amplitude of the capacitance scale value narrows: 724–727mV in the first round → 717–722mV in the second round → 708–712mV in the third round, and the total drift across the three rounds is much smaller than that of the bare Pt probe; the contrast ratio of light and dark on both sides of the MoS2 step and the noise intensity of the transverse stripes do not deteriorate significantly, and the distribution pattern of the interface capacitance can be repeatedly observed. The HfO2 ultrathin coating has a uniform and controllable thickness, and as a stable fixed dielectric layer, it is introduced into the tip-sample gap, eliminating the continuous decay of the interface capacitance caused by the dynamic growth of the Pt oxide layer. Under multiple scans, the quantitative capacitance value has only a small and negligible drift, enabling continuous and stable quantitative testing of the carrier distribution on the MoS2 surface.

[0052] In summary, the uncoated Pt tip continuously oxidizes and adsorbs contaminants during atmospheric scanning, resulting in significant distortion of the dC / dV amplitude contrast across three scans, a substantial and continuous decrease in the quantitative value of the interface capacitance, and extremely poor stability of the electrical signal; the morphology height channel exhibits only a slight scale shift. The dense HfO2 passivation layer on the tip surface effectively isolates metal oxidation and surface contamination. Under three consecutive scans, the dC / dV amplitude contrast distributions highly overlap, the drift amplitude of the interface capacitance value is significantly reduced, and both the morphology and electrical imaging signals demonstrate excellent repeatability, proving that the HfO2 coating can effectively improve the long-term electrical characterization stability of two-dimensional materials using C-AFM.

[0053] Figure 6 This is a comparison chart of the standard deviation of the dC / dV amplitude signal as a function of scan duration. Figure 6As can be seen, for the pure Pt probe (black curve): in the initial stage of testing (0s), the standard deviation of the dC / dV amplitude of the uncoated probe is close to 28 a.u., which is at an extremely high level; as the scanning time increases to 600s, the standard deviation gradually decreases to a minimum value of about 13.5 au. This is because: the surface of the bare Pt tip is clean when it is first used; during the scanning process under atmospheric conditions, the tip rapidly generates an uneven Pt oxide layer, adsorbs water vapor and hydrocarbon impurities, the work function of the tip surface and the dielectric layer at the tip continuously change dynamically, the electrostatic force and differential capacitance response of the tip-MoS2 interface are disordered over a wide range, and the local contrast difference of the image is extremely large, so the initial standard deviation is extremely high; at 600s, the oxidation and adsorption of the tip surface tend to reach a stage of saturation, and the signal fluctuation narrows slightly, but the overall standard deviation is still significantly higher than that of the coated probe. After scanning for more than 600s, the black curve rises sharply, reaching a peak of about 24 a.u. at 750~800s, and then falls back slightly. The reasons are twofold: ① Prolonged scanning friction causes wear and localized deformation of the pure Pt soft tip, continuously altering the effective detection curvature of the tip; ② Localized peeling of the oxide layer and uneven adhesion of MoS2 nanoparticles to the tip tip surface cause a severe disruption in the spatial distribution of electrical properties on the tip surface, resulting in large-area contrast shifts, stripe noise, and abrupt changes in brightness contrast in the entire SCM image. Ultimately, this manifests as a significant spike in the standard deviation of dC / dV amplitude, completely losing its stable quantitative characterization capability. Therefore, the entire black curve exhibits extremely large fluctuations, spanning a range of 13.5–28 a.u., and under prolonged continuous scanning, the SCM electrical signal lacks a stable range, making it impossible to achieve repeatable quantitative acquisition of the MoS2 surface capacitance signal. The probe obtained in this embodiment (red curve) maintains a narrow oscillation within a small range of 10.5~13.5 au throughout the entire red curve, without any sharp rises or falls, demonstrating significant stability. This is because HfO2 is a dense, chemically inert, high-hardness insulating dielectric film that completely encapsulates the Pt tip metal substrate, fundamentally isolating three factors that cause instability: blocking Pt from contact with air and moisture, inhibiting tip oxidation; blocking the adsorption of environmental pollutants and MoS2 sample debris; and improving the mechanical wear resistance of the tip, slowing down tip wear and deformation. Throughout the continuous scanning process, the electrical and geometric states of the tip surface remain essentially constant, the interfacial differential capacitance between the tip and MoS2 is uniform and stable, and the contrast distribution of the entire dC / dV amplitude image shows no significant drift or distortion. Therefore, the signal standard deviation remains at a low level with minimal fluctuations. The slight fluctuations in the curve are only due to the inherent weak noise of the SCM testing system and the small signal differences caused by natural defects in the sample itself, which are normal fluctuations in the instrument background and do not affect long-term continuous characterization. Therefore, Figure 6It can be seen that the standard deviation of the signal of the uncoated probe remains high throughout the entire process and undergoes drastic changes with the scanning time, indicating extremely poor stability of the SCM electrical signal under long-term scanning. In this embodiment, the standard deviation of the signal of the probe remains stable in the low value range for a long time, and the fluctuation range is significantly narrowed, proving that the tip protective layer can effectively suppress signal distortion caused by oxidation, adsorption and wear, and greatly improve the long-term stability of MoS2 scanning capacitance microscopy characterization.

[0054] Figure 7 This is a comparison of the standard deviation of capacitance signal over time. The pure Pt probe (black curve) exhibits high values ​​and large, irregular oscillations throughout, with a standard deviation ranging from approximately 450–930 au, showing extreme fluctuations. Throughout the testing period, the standard deviation of the uncoated probe's capacitance is consistently much higher than that of the coated probe, with the baseline remaining above 600 au. This indicates that during testing with the bare Pt tip, the baseline capacitance signal in the entire MoS2 region fluctuates drastically. It reaches a peak of approximately 930 au around 300 s, drops to a trough of approximately 620 au at 500 s, falls again to a secondary trough of approximately 450 au at 750 s, and then rises back to 770 au at 900 s, without a stable range. The surface state of the probe tip is irreversibly altered in each scan, and the degree of capacitance response shift varies across different regions of the image, ultimately resulting in drastic fluctuations in the overall standard deviation, making quantitative and repeatable characterization of the capacitance signal impossible.

[0055] In this embodiment, the red curve shows a significantly lower baseline, with the standard deviation remaining stable within a narrow range of 230–460 au, and fluctuations are greatly suppressed. The baseline is significantly reduced, with the standard deviation of the coated probe capacitance being only about half that of the uncoated probe throughout the entire time period, resulting in a significant improvement in overall signal uniformity. The oscillation amplitude is extremely small, with no extreme abrupt changes. The curve only exhibits small, gentle fluctuations, with a small trough (240 au) occurring only at 500 s, without the doubling-like dramatic rises and falls seen with bare Pt probes. The minor fluctuations are only due to the instrument's background noise and the natural contrast differences caused by inherent defects in the MoS2 sample, which are normal minor disturbances in the testing system. This quantitative standard deviation curve is digitally supported by the capacitance mapping images in Figures 4 and 5: the continuous shift of the capacitance scale of the bare Pt probe, the increased noise of the horizontal stripes in the image, and the continuous change in the step contrast observed by the naked eye are transformed into quantifiable high standard deviation and violent fluctuations in this figure; while the contrast of the coated probe image is stable and the scale drift is weak, corresponding to the curve characteristics of low standard deviation and small oscillations in this figure, forming a complete chain of evidence of "visual image phenomena + quantitative statistical data".

[0056] Figure 8 shows the results of two SCM single-point CV repeat scans performed by the probe at the same location on MoS2 in this embodiment. Figure 8 It can be seen that the two test curves of the three sets of signals—dC / dV amplitude, phase, and interface capacitance—highly overlap, and there is no significant shift in the curve trend, peak position, or numerical baseline across the entire bias range (-3 V to 0 V). The dense HfO2 protective layer isolates the Pt tip from oxidation and contaminant adsorption, and the dielectric structure and contact barrier at the tip-sample interface remain constant during repeated tests, stably reproducing the intrinsic capacitance-bias response of MoS2. The single-point electrical test repeatability is excellent.

[0057] Figure 9 shows the results of two SCM single-point CV repeat scans at the same location on MoS2 using a bare Pt probe without coating. Significant separation and baseline drift were observed in the two scan curves for all three signal sets. Irreversible deviations were found in the peak amplitude of the differential capacitance, the overall phase baseline, and the interface capacitance value. Under atmospheric conditions, the bare Pt tip rapidly forms an oxide layer and adsorbs impurities during the first scan, continuously altering the electrical properties of the tip surface. This results in a systematic distortion of the interface differential capacitance response in the second test, making repeatable quantitative CV characterization impossible. This clearly demonstrates the extremely poor stability of the electrical signal from the unprotected tip.

[0058] Example 2 A method for preparing a probe coating for scanning capacitance microscopy testing, such as Figure 1 As shown, it includes the following steps: S1. Provide a conductive probe substrate and use atomic layer deposition process to fix the conductive probe substrate on the wafer base of the atomic layer deposition equipment; S2. Heat the hafnium source precursor delivery valve bank to 130.0°C (for vaporizing the hafnium source precursor); heat the process chamber to 200.0°C; heat the wafer pedestal that holds the conductive probe to 200.0°C; S3. Introduce the hafnium source precursor into the reaction chamber and perform 100 complete deposition cycles to deposit a hafnium oxide barrier layer on the surface of the conductive probe substrate, thereby obtaining the probe used for scanning capacitance microscopy testing.

[0059] The hafnium source precursor is 3-TDMAHf.

[0060] The conductive probe substrate is pure Pt; its spring constant is 22 N / m, its frequency is 21 kHz, its length is 300 μm, its width is 100 μm, its thickness is 5 μm, and it is a rectangular solid wire.

[0061] The thickness of the hafnium oxide barrier layer is 10 nm.

[0062] A single complete deposition process includes: a hafnium source precursor pulse and an oxidant pulse. The hafnium source precursor pulse duration is 100 ms, and the oxidant pulse duration is 50 ms.

[0063] The oxidant is H2O.

[0064] Comparative Example 1 A method for preparing a probe coating for scanning capacitance microscopy testing, such as Figure 1 As shown, it includes the following steps: S1. Provide a conductive probe substrate and use atomic layer deposition process to fix the conductive probe substrate on the wafer base of the atomic layer deposition equipment; S2. Heat the hafnium source precursor delivery valve bank to 130.0°C (for vaporizing the hafnium source precursor); heat the process chamber to 200.0°C; heat the wafer pedestal that holds the conductive probe to 200.0°C; S3. Introduce the hafnium source precursor into the reaction chamber and perform 150 complete deposition cycles to deposit a hafnium oxide barrier layer on the surface of the conductive probe substrate, thereby obtaining the probe used for scanning capacitance microscopy testing.

[0065] The hafnium source precursor is 3-TDMAHf.

[0066] The conductive probe substrate is pure Pt; its spring constant is 22 N / m, its frequency is 21 kHz, its length is 300 μm, its width is 100 μm, its thickness is 5 μm, and it is a rectangular solid wire.

[0067] The thickness of the hafnium oxide barrier layer is 15 nm.

[0068] A single complete deposition process includes: a hafnium source precursor pulse and an oxidant pulse. The hafnium source precursor pulse duration is 100 ms, and the oxidant pulse duration is 50 ms.

[0069] The oxidant is H2O.

[0070] Comparative Example 2 A method for preparing a probe coating for scanning capacitance microscopy testing, such as Figure 1 As shown, it includes the following steps: S1. Provide a conductive probe substrate and use atomic layer deposition process to fix the conductive probe substrate on the wafer base of the atomic layer deposition equipment; S2. Heat the hafnium source precursor delivery valve bank to 130.0°C (for vaporizing the hafnium source precursor); heat the process chamber to 200.0°C; heat the wafer pedestal that holds the conductive probe to 200.0°C; S3. Introduce the hafnium source precursor into the reaction chamber and perform 150 complete deposition cycles to deposit a hafnium oxide barrier layer on the surface of the conductive probe substrate, thereby obtaining the probe used for scanning capacitance microscopy testing.

[0071] The hafnium source precursor is 3-TDMAHf.

[0072] The conductive probe substrate is pure Pt; its spring constant is 22 N / m, its frequency is 21 kHz, its length is 300 μm, its width is 100 μm, its thickness is 5 μm, and it is a rectangular solid wire.

[0073] The thickness of the hafnium oxide barrier layer is 20 nm.

[0074] A single complete deposition process includes: a hafnium source precursor pulse and an oxidant pulse. The hafnium source precursor pulse duration is 100 ms, and the oxidant pulse duration is 50 ms.

[0075] The oxidant is H2O.

[0076] Figure 10 The figure shows a comparison of IV curves for probes with HfO2 coatings of different thicknesses. As can be seen from the figure, the curves for 5 nm (red solid line) in Example 1 and 10 nm (green solid line) in Example 2 closely follow the zero-current baseline throughout, with no significant tunneling current in either the positive or negative bias range, and the leakage current value remains stably around 0 A. Ultrathin HfO2 possesses dense, pinhole-free insulating properties; thicknesses of 5 nm and 10 nm are sufficient to form a complete barrier layer, blocking the direct tunneling path between the Pt tip and the MoS2 sample. The interface has almost no charge transport, and no additional leakage current interferes with the acquisition of differential capacitance signals, making it suitable for the weak capacitance signal detection requirements of SCM. The 15 nm (blue scattered dots) thick coating probes in Comparative Example 1 and 20 nm (light pink scattered dots) thick coating probes in Comparative Example 2 exhibit significant tunneling current after |V| > 0.5 V. The larger the absolute value of the bias voltage, the higher the current amplitude, and the current fluctuation range and peak current of the 20 nm coating are greater than those of the 15 nm coating. As the thickness of HfO2 increases, the number of internal defects and interface stress defects in the coating increases. Under high bias voltage, electrons can tunnel through the defects in the dielectric layer, resulting in a large fluctuation in leakage current. The drastic changes in tunneling current will superimpose and mask the intrinsic differential capacitance response of MoS2, seriously interfering with the quantitative accuracy of SCM electrical imaging.

[0077] In summary, this invention provides a method for preparing a probe coating for scanning capacitance microscopy (SCM) testing. This invention employs atomic layer deposition (ALD) technology, with precise segmented temperature control of the ALD equipment, to prepare an ultrathin hafnium oxide (HfO2) barrier layer on the surface of a conductive probe substrate. This layer provides a probe coating that simultaneously meets the requirements of charge blocking injection and maintaining capacitance sensitivity. The dc / dV amplitude and capacitance signal remain stable across multiple scans (200-1000 s) (higher average value, smaller standard deviation / Alpe bias). As a high-k dielectric layer, the hafnium oxide (HfO2) barrier layer allows for the in-situ construction of a complete and stable metal-oxide-semiconductor (MOS) test structure during measurement, physically isolating the charge injection channel between the probe and the bare semiconductor surface, allowing for reliable CV measurements (consistent repeatable curves from -3 to 0 V). CAFM testing shows the coating is intact (current ~pA level, noise dominant).

[0078] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A method for preparing a probe coating for scanning capacitance microscopy testing, characterized in that, Includes the following steps: S1. Provide a conductive probe substrate and use atomic layer deposition process to fix the conductive probe substrate on the wafer base of the atomic layer deposition equipment; S2. Heat the hafnium source precursor delivery valve assembly to 120-140°C; heat the reaction chamber to 150-350°C; heat the wafer base that fixes the conductive probe substrate to 150-350°C; S3. Introduce the hafnium source precursor into the reaction chamber and perform 50-100 complete deposition cycles to deposit a hafnium oxide barrier layer on the surface of the conductive probe substrate, thereby obtaining the probe coating for scanning capacitance microscopy testing.

2. The method for preparing a probe coating for scanning capacitance microscopy testing according to claim 1, characterized in that, The hafnium source precursor is tetra(dimethylamino)hafnium, tetra(ethylmethylamino)hafnium, or tetra(diethylamino)hafnium.

3. The method for preparing a probe coating for scanning capacitance microscopy testing according to claim 1, characterized in that, The conductive probe substrate is a pure Pt conductive probe substrate.

4. The method for preparing a probe coating for scanning capacitance microscopy according to claim 3, wherein the thickness of the hafnium oxide barrier layer is 3-10 nm.

5. The method for preparing a probe coating for scanning capacitance microscopy testing according to claim 1, characterized in that, The complete deposition process described in a single instance includes: a hafnium source precursor pulse and an oxidant pulse.

6. The method for preparing a probe coating for scanning capacitance microscopy testing according to claim 5, characterized in that, The hafnium source precursor pulse duration is 40-400ms, and the oxidant pulse duration is 30-60ms.

7. A method for preparing a probe coating for scanning capacitance microscopy testing according to claim 5, characterized in that, The oxidant is H2O.